What lies beyond—Insights into elastic microscaffolds with metamaterial properties for cell studies - Fladung, Magdalena; Berkes, Alexander; Alletzhaeusser, Tim; Chen, Yi; Munding, Natalie; Tanaka, Motomu; Wegener, Martin; Bastmeyer, Martin (Current opinion in biomedical engineering, 2025)
Recent advances in additive manufacturing have opened up new possibilities to print almost arbitrary structures with submicrometer resolution. An intriguing application is the fabrication of metamaterial-based scaffolds with unprecedented precision and with defined effective elastic properties for mechanobiological research. This field of study has already led to promising results but remains wide open. The vast possibilities, together with the high interdisciplinary character and current lack of established protocols or literature on the subject, are intriguing on the one hand but might discourage researchers who are new to this field. In this review, we aim to provide insights into the work with such microstructured bio-metamaterials, mainly based on our own experience with 2D systems, hoping to encourage further mechanobiological studies. Finally, we present some considerations for expanding to the third dimension to more closely resemble the invivo situation.